Cultural networks in migrating heritage : intersecting theories and practices across Europe - Innocenti, Perla (Ashgate, 2015)
"This book highlights the strengths and benefits from new cultural networking practices but also the challenges and issues that arise, how these could be addressed and what lessons can be learnt. It also sets out to answer the questions 'how.' How can we leverage the power of cross-border cultural networks in a contested place such as Europe today? How can European cultural institutions elaborate the necessary approaches and strategies to achieve a type of cultural cooperation that is truly based on cultural practice? How can the actions of the European Commission and relevant cultural bodies in Europe be strengthened, adapted or extended to meet these goals?"--Provided by publisher.